Ethical Leadership of Khulafaur Rasyidin: Modern Relevance and Values: English - Lubiana Yubawa (International Journal of Emerging Issues in Islamic Studies, 2025)
This study examines the ethical values and moral responsibilities embedded in the leadership of Khulafaur Rasyidin and their relevance to the challenges of modern leadership. Employing a literature review method, the study focuses on classical Islamic sources such as the Qur'an, Hadith, and historical commentaries (sirah and tafsir) to extract core principles of Islamic leadership. The interpretive approach used is normative-ethical, analyzing the leadership practices of Abu Bakar, Umar, Utsman, and Ali through the lens of Islamic moral philosophy. Key leadership values identified include amanah (trustworthiness), ‘adl (justice), shura (consultation), and spiritual accountability to God and society. The findings reveal that their leadership reflects a model of transcendental ethics that integrates moral, spiritual, and administrative dimensions. This framework offers a valuable paradigm for addressing contemporary leadership crises marked by declining public trust and ethical deficits. The study concludes that integrating prophetic ethical principles into modern leadership and policy-making contexts can enhance moral governance and foster sustainable, people-centered leadership in both public and private sectors. Despite its non-empirical nature, the study makes a theoretical contribution to the discourse on ethical leadership grounded in Islamic tradition.